Service quality and customer satisfaction: a study of Asajaya District Office Counter Service / Muhammad Azam Julaihi - Julaihi, Muhammad Azam (2016)
In today’s, service quality mostly important to all the organization which for public sectors or private sectors. The excellent service quality make a customer to be satisfactions. Service quality and customer satisfaction have a strong relationship to all the organization. This is because satisfactions can give the knowledge in order to improve the service quality that has been provided to the customers. The current study is made to address the issues by proposing a theoretical framework for this quantitative study on the service quality and customer satisfaction towards counter service. In addition, the customer satisfaction based on the service quality dimensions. This study will focus on the respondent who come to seek services at Asajaya District Office.